Measurement and analysis of the production function of the transport sector in the Iraqi economy - عبد الحميد, مناهل مصطفى; علوان, غفران حاتم (Journal of Economics and Administrative Sciences, 2011)
Transportation Sector classified as one of the services sectors which is without the production activities cannot be complete its rule. Is act asmoving actions which operate at production and non production goals for the organization and individuals insides the country and with others, that is why this sector act as one of the main which is occupied an important status on the way the economic activities and on the level of the economic institutions the transportation work on transforming all the commodities and products from productions locations to consumption location then its effect the productivity process and create the location utility and on the level of economic it considered as one of the economic supportive structure and active factor on activation of other economic branches and for the reason of understanding the motive at this sector and the rule of the production process at mention the measurement and analyze the production function to recognize the production level which passed by and on the rule of the factors which effective the production  process for this sector and the reason of giving more interests in this sector to achieve the quantitative and qualitative progress to serve the economic and social at Iraq development we dividel the research two parts:    The first part: theoretical frame    The second part: practical frame  The theoretical frame contains the theoretical part to introduce theoretical frame to the production function and to recognize the economical and social rule to transportation sector and the most important economic indicators to it and the practical frame presents a building multi liner model to estimate the production function (cop- doclas).For the transportation sector at Iraq for the period 1990-2007, and it,s clear that the, and shows that the results at this sector pass on stage of the diminishing return and the technical factor has a big effect on this function.